NGHIÊN CỨU HIỆU ỨNG ĐỒNG VẬN CẮT MẠCH CHITOSAN BẰNG BỨC XẠ GAMMA Co-60 KẾT HỢP VỚI HYDROPEROXIT - Hiến, Nguyễn Quốc; Phú, Đặng Văn; Kim Lan, Nguyễn Thị; Duy, Nguyễn Ngọc; Ái Trinh, Nguyễn Thuỵ; Du, Bùi Duy (Vietnam Journal of Chemistry, 2012)
Chitosan from squid pens with deacetylation degree of about 70% and molecular weight (Mw0) 91.5 ´ 103 in dilute lactic acid solution containing H2O2 (1%) was effectively degraded by irradiation with gamma Co-60 radiation (1.33 kGy/h) in dose range up to 16 kGy. Based on the results of Mw measured by gel permeation chromatography (GPC), the synergic effect for degradation of chitosan was calculated to be of 58.4% at 4 kGy and gradually decreased to 0.2% at 16 kGy. The values of radiation scission yield (Gs) were found out to be 2.2 and 0.2 mmol/J for chitosan in solution of 5% with and without H2O2 (1%), respectively. Deacetylation degrees of degraded chitosan measured from infrared (IR) spectra were almost unchanged.